Bufalin Inhibits HCT116 Colon Cancer Cells and Its Orthotopic Xenograft Tumor in Mice Model through Genes Related to Apoptotic and PTEN/AKT Pathways. (7th December 2015) - Wang, Jie; Chen, Chao; Wang, Shiying; Zhang, Yong; Yin, Peihao; Gao, Zhongxiang; Xu, Jie; Feng, Dianxu; Zuo, Qinsong; Zhao, Ronghua; Chen, Teng
Abstract : Aims . To investigate the anticolorectal cancer (CRC) effects of Bufalin, a bioactive polyhydroxysteroid from Venenum Bufonis, using HCT116 human CRC cell and an established orthotopic xenograft model in mice, and to explore the mechanisms of action. Material and Methods . Cultured HCT116 cells or BALB/c mice with orthotopic tumor were treated by Bufalin (positive control: 5-FU). Cell proliferation, apoptosis, and cycling were determined by MTT, Annexin V/PI staining, and flow cytometry, respectively. In mice, tumor inhibition rate and animal survival were calculated. The expressions of PTEN/phosphate-PTEN, AKT/phosphate-AKT, Bad, Bcl-xl, Bax, or Caspase-3 in cells and/or tumors were determined by Western blot or immunohistochemical staining. Results . Bufalin significantly inhibited cell proliferation and induced cell apoptosis and cycle arrest in a dose/time-dependent manner. In the animal model, Bufalin treatment resulted in significant inhibition of tumor growth and prolonged survival. In the Bufalin-treated cultured cells and/or xenograft tumors, the expressions of PTEN, Bad, Bax, and Caspase-3 were significantly increased, while p-AKT and Bcl-xL significantly decreased. Conclusions . Our results indicate that Bufalin inhibit cell proliferation and orthotopic tumor growth by inducing cell apoptosis through the intrinsic apoptotic pathway, which is of pivotal significance in the identification of an anticancer drug that may synergize with Bufalin.